A Comprehensive Assessment of the Antioxidant Capacity of Varied Bacopa Monnieri Extracts and Its Toxicity on Early Life Stages of Zebrafish Embryos - Shanmugam R.; Arthi B.; Pragya P.; Girigoswami A.; Koyeli G.; Pemula G.; Senthilkumar N.; Arumugam V.A. (My University, 2025)
Background: Bacopa monnieri is an herbal plant used predominantly in Ayurvedic medicine. Though this plant has pharmacological properties, it is pivotal to acknowledge its antioxidant capacity and toxicological properties which are not well established. Objectives: The principal aim of this study is to elucidate the antioxidant capacity and toxicological properties of B. monnieri leaf extracts in the early life stages of Danio rerio (zebrafish) embryos. Methods: This was a comparative identification of the antioxidant capacities of five different extracts of aqueous, ethanol, acetone, chloroform, and petroleum ether of B. monnieri leaf by investigating through in vitro antioxidant assays such as Diphenyl-1-Picrylhydrazyl (DPPH), azinobis[3-Ethylbenzothiazoline-6-Sulfonate] (ABTS), ferric reducing antioxidant power (FRAP), and total antioxidant capacity (TAC) and enzymatic assays such as SOD, CAT, Px, AO, and PPO. Additionally tested for the qualitative and quantitative estimation of phytochemicals. Furthermore, the Fish Embryo Toxicity (FET) assay has been performed to analyze the developmental deformities, lethal and sublethal toxic effects, hatch rate, heart rate, and survival of zebrafish embryos upon treatment with the aqueous plant extract. Result: The results showed the availability of polyphenols and non-phenolic macromolecules. Total phenol and flavonoid content were greater in the aqueous extract and tannin content was higher in ethanol extract. Among the five extracts, the aqueous extract showed greater antioxidant and free radical scavenging activities. Furthermore, the investigation addressed the toxicological effects of aqueous extract on zebrafish embryos that resulted in the least developmental abnormalities and delayed hatching rate at greater concentrations along with 100% mortality at 96 h Post Fertilization (hpf) of higher concentrations. Conclusion: The results indicate that B. monnieri may serve a strong prophylactic action against reactive oxygen species-related diseases with the least sublethal effects. © The Author(s) 2025.